An approximation method for analysis and valuation of credit correlation derivatives - Egami, Masahiko; Esteghamat, Kian (Journal of Banking & Finance, 2006)
This paper presents a model for approximating the value of a basket of default-correlated assets and analyzes subordinate tranches in securitized debt obligations. The model is calibrated to an intensity-based simulation of correlated defaults and represents an alternative computation method to full Monte Carlo simulation. Timing of individual obligor defaults are driven by intensity processes and collateral value is modeled with a jump-diffusion process where the number of jumps corresponds to the total number of defaults in the asset pool. This approach allows decomposition of subordinate obligations in terms of a collection of simpler securities and yields useful risk management information.